Self-Awareness in thr Work of Enhancing the Authentic Leadership of the Headmaster of Madrasah Aliyah Negeri in Riau Province - Agung Setiabudi; Mukhtar Mukhtar; Wahyudi Wahyudi (Edumaspul: Jurnal Pendidikan, 2024)
Self-awareness plays a crucial role in the development of authentic leadership, particularly for the headmasters of Madrasah Aliyah Negeri (MAN) in Riau Province. Authentic leadership refers to a leadership style that emphasizes transparency, ethical behavior, and self-awareness, fostering an environment where followers feel valued and supported. This study explores how self-awareness in the work of headmasters can enhance their leadership effectiveness in improving the quality of education and the religious behavior of students. Through qualitative research methods, including interviews and observations, this study investigates the practices, challenges, and strategies employed by the headmasters in fostering an authentic leadership style. The findings indicate that self-awareness allows headmasters to recognize their strengths and weaknesses, reflect on their actions, and adapt their leadership approach to better align with the school’s values and goals. Furthermore, headmasters who demonstrate a high level of self-awareness are more capable of creating a positive school culture, building trust with teachers and students, and guiding the school toward continuous improvement. This study contributes to the understanding of the role of self-awareness in the leadership development of school heads, particularly in the context of Madrasah Aliyah Negeri in Riau Province. By enhancing self-awareness, headmasters can effectively lead their schools towards achieving educational excellence while fostering a religious and moral environment for students